Myeloablation followed by autologous stem cell transplantation normalises systemic sclerosis molecular signatures. Issue 10 (7th August 2019) - Assassi, Shervin; Wang, Xuan; Chen, Guocai; Goldmuntz, Ellen; Keyes-Elstein, Lynette; Ying, Jun; Wallace, Paul K; Turner, Jacob; Zheng, W Jim; Pascual, Virginia; Varga, John; Hinchcliff, Monique E; et al.
Abstract : Objective: In the randomised scleroderma: Cyclophosphamide Or Transplantation (SCOT trial) (NCT00114530 ), myeloablation, followed by haematopoietic stem cell transplantation (HSCT), led to improved clinical outcomes compared with monthly cyclophosphamide (CYC) treatment in systemic sclerosis (SSc). Herein, the study aimed to determine global molecular changes at the whole blood transcript and serum protein levels ensuing from HSCT in comparison to intravenous monthly CYC in 62 participants enrolled in the SCOT study. Methods: Global transcript studies were performed at pretreatment baseline, 8 months and 26 months postrandomisation using Illumina HT-12 arrays. Levels of 102 proteins were measured in the concomitantly collected serum samples. Results: At the baseline visit, interferon (IFN) and neutrophil transcript modules were upregulated and the cytotoxic/NK module was downregulated in SSc compared with unaffected controls. A paired comparison of the 26 months to the baseline samples revealed a significant decrease of the IFN and neutrophil modules and an increase in the cytotoxic/NK module in the HSCT arm while there was no significant change in the CYC control arm. Also, a composite score of correlating serum proteins with IFN and neutrophil transcript modules, as well as a multilevel analysis showed significant changes in SSc molecular signatures after HSCT while similar changes were not observed in the CYC arm. Lastly, a decline in the IFN and neutrophil modules was associated with an improvement in pulmonary forced vital capacity and an increase in the cytotoxic/NK module correlated with improvement in skin score. Conclusion: HSCT contrary to conventional treatment leads to a significant 'correction' in disease-related molecular signatures.